2016
DOI: 10.21873/anticanres.11260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significances of Preoperative Classification of Intrahepatic Cholangiocarcinoma: Different Characteristics of Perihilar vs. Peripheral ICC

Abstract: Abstract. Background: The aim of this study was to evaluate the clinical significance of preoperative classification of intrahepatic cholangiocarcinoma (ICC) into perihilar and peripheral types using dynamic computed tomography (CT). Patients and MethodsEven though intrahepatic cholangiocarcinoma (ICC) is a relatively rare disease, it is the second most common primary liver malignant tumor after hepatocellular carcinoma (HCC), and has a relatively highly prevalence in Asia and the U.S.A., with over 1/100,000 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…It is widely acknowledged that the curative treatment of IHCC is surgical resection. Despite the surgical advances and risk factors for IHCC, the clinical outcome after resection is still dismal [13,14]. Consequently, the 5-year survival rate in our institution was 33.3%, which was comparable to the previously reported survival rates [11,13,15,16].…”
Section: Discussionsupporting
confidence: 75%
“…It is widely acknowledged that the curative treatment of IHCC is surgical resection. Despite the surgical advances and risk factors for IHCC, the clinical outcome after resection is still dismal [13,14]. Consequently, the 5-year survival rate in our institution was 33.3%, which was comparable to the previously reported survival rates [11,13,15,16].…”
Section: Discussionsupporting
confidence: 75%
“…The hilar type ICCs originated from intrahepatic large biliary ducts are likely to show aggressive course with metastatic potential. Though tumor localization could be classified according to radiological findings in this study, classification based on radiological findings has been reported to accurately reflect histomorphological typing [33,34]. In fact, hilar type ICC, defined by radiological localization in this study, showed higher recurrence rate and poorer survival than peripheral type.…”
Section: Plos Onementioning
confidence: 73%
“…Surgical techniques. The details of our surgical techniques and the follow-up methods have been reported (1,9,12,13). Major hepatic resection (HR) with bile duct resection was performed when bile duct invasion of ICC was suspected to have affected the first hepatic duct.…”
Section: Methodsmentioning
confidence: 99%
“…However, the surgical outcomes for ICC remain unsatisfactory with a 5-year survival rate of 23.6-35% (1,4,7,8) and 58% even after R0 resection (1,9). The rate of recurrence was also reported to be high, at 53-71% (4,10,11).…”
mentioning
confidence: 99%